2020
DOI: 10.1101/2020.04.02.022368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Membrane Proteins Have Distinct Fast Internal Motion and Residual Conformational Entropy

Abstract: AbstractFor a variety of reasons, the internal motions of integral membrane proteins have largely eluded comprehensive experiential characterization. Here, the fast side chain dynamics of the 7-transmembrane helix protein sensory rhodopsin II and the beta-barrel bacterial outer membrane channel protein W have been characterized in lipid bilayers and detergent micelles by solution NMR relaxation techniques. Though of quite different topologies, both proteins are found to have a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This substantiates our recurrence analysis 50 , in that, uOmpX aq does not behave like a fully unfolded, random coil polypeptide. uOmpX aq thus exhibits a multi-tier dynamical character with fast and slow intrachain motions, as has been previously observed for other proteins and membrane proteins 5355 .…”
Section: Resultssupporting
confidence: 72%
“…This substantiates our recurrence analysis 50 , in that, uOmpX aq does not behave like a fully unfolded, random coil polypeptide. uOmpX aq thus exhibits a multi-tier dynamical character with fast and slow intrachain motions, as has been previously observed for other proteins and membrane proteins 5355 .…”
Section: Resultssupporting
confidence: 72%
“…The strategy was also applied to obtain mechanistic insights into allosteric regulation of the A 2A R by physiological cations [ 56 ] and ligand-dependent conformational equilibria in the transmembrane regions in β 1 AR [ 57 ]. It should also be noted that fast methyl dynamics were quantified in the presence of different ligands in A 2A R by using triple-quantum relaxation data [ 58 ], as well as in sensory rhodopsin II [ 59 ] and bacteriorhodopsin [ 60 ].…”
Section: G-protein Coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…On average, membrane proteins have a larger fraction of the number of residues which contact cavities than globular proteins (19). A recent NMR relaxation study shows that the internal side chains of folded membrane proteins are highly dynamic compared to those of globular proteins (24). This implies that membrane proteins may not be as tightly packed as globular proteins, and the resulting low sidechain entropic cost can significantly compensate the lack of the hydrophobic effect as a driving force for membrane protein folding (24).…”
Section: Significancementioning
confidence: 99%
“…An experimental study has shown that cavity hydration can stabilize a globular protein by 1.5 kcal/mol to 2.0 kcal/mol (78). Therefore, for both globular and membrane proteins, cavity solvation by either water or lipids can counterbalance the energetic cost caused by the loss of protein packing (24).…”
Section: Do Native Cavities Compromise Stability?mentioning
confidence: 99%